New and notable stomatopods (Crustacea, Stomatopoda) from Mozambique - Brokensha, Rouane; Landschoff, Jannes; Griffiths, Charles (European Journal of Taxonomy, 2023)
New and notable stomatopods are reported on and added to the Mozambican faunal list, based principally on material housed in the collections of the Iziko South African Museum. Seven species are reported for the first time from Mozambican waters including one undescribed species of Clorida Eydoux & Souleyet, 1842, bringing the total known Mozambican stomatopod fauna to 22 species, comprising 17 genera and eight families. The known fauna is tabulated and taxonomic accounts of eight species are given, seven of these representing the new species records including one undescribed species, while the eighth species account is of the previously poorly documented Erugosquilla woodmasoni (Kemp, 1911), which is reported on from unpublished material. The new record of Manningia australiensis Manning, 1970 represents the first record of the family Eurysquillidae from southern Africa.